(3bQGAI SjchdhLjI aj gehe GdfGS (B/ s - (3GdTQHjfj, dWaj YHO GdYRjR,s 1951- ((3OShb (B[(3eUQ(B] :s (3OGQ GdYde hGdEjeGf ddfTQ hGdJhRjY ;s (3GdLRGFQ (B:s (3OGQ GdLOjO ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd gPG GdcJGH eONd Edi JYQja GdhUeI hGdCeQGV GdfaSjI hGdYbdjI hMbGFb heYdheGJ hUeI GdChgGe hGdNQGaGJ Yf GdeQV GdfaSj hhUeI GdLfhf aj GdWH GdfaSj hGdMjGI hGdhUeI hCfhGY ef GdGVWQGHGJ GdfaSjI hXGgQI GdhUeI aj GdeLJeYGJ GdYQHjI hMbhb GdeQjV GdfaSj hLhGfH bGfhfjI hTQYjI aj GdCeQGV GdYbdjI hGdhUeI hGYJHGQGJ CNdGbjI hGdefXhQ GdESdGej ddCeQGV GdfaSjI hGdhUeI hYdGL GdCeQGV GdfaSjI(B.s
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
(3jTJed Ydi HHdjhLQGajI(B. s
Keywords: (3GdeTcdGJ GdfaSjIs; (3GdWH GdfaSjs